2019
DOI: 10.3389/fphar.2019.00379
|View full text |Cite
|
Sign up to set email alerts
|

Role of TREK-1 in Health and Disease, Focus on the Central Nervous System

Abstract: TREK-1 is the most studied background K 2P channel. Its main role is to control cell excitability and maintain the membrane potential below the threshold of depolarization. TREK-1 is multi-regulated by a variety of physical and chemical stimuli which makes it a very promising and challenging target in the treatment of several pathologies. It is mainly expressed in the brain but also in heart, smooth muscle cells, endocrine pancreas, and prostate. In the nervous system, TREK-1 is involved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
68
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(68 citation statements)
references
References 117 publications
0
68
0
Order By: Relevance
“…TREK-1 is a background potassium channel, the protagonist in multiple key physiological functions and pathophysiological conditions in nervous and cardiovascular tissue including neuroprotection, depression, epilepsy, pain, ischemia, and atrial fibrillation (Djillani et al, 2019). We have previously shown pharmacological evidence that implicates TREK-1 as a major potassium conductance regulating gastrointestinal smooth muscle contractility (Ma et al, 2018), providing a potential therapeutic target for motility disorders.…”
Section: Discussionmentioning
confidence: 99%
“…TREK-1 is a background potassium channel, the protagonist in multiple key physiological functions and pathophysiological conditions in nervous and cardiovascular tissue including neuroprotection, depression, epilepsy, pain, ischemia, and atrial fibrillation (Djillani et al, 2019). We have previously shown pharmacological evidence that implicates TREK-1 as a major potassium conductance regulating gastrointestinal smooth muscle contractility (Ma et al, 2018), providing a potential therapeutic target for motility disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Researches have demonstrated that the two pore potassium channel TREK-1 plays the protective role in central nervous disorders (Djillani et al 2019). However, to our best knowledge, no ndings concerned about the role of TREK-1 in AD.…”
Section: Discussionmentioning
confidence: 96%
“…Differential DNA methylation in PMG cases with 1q trisomy affected not only regions on the long arm of chromosome 1, but also was seen in other autosomes and mapped to several genes associated with brain function, malformation, epilepsy, developmental delay, and autism (Supplement Fig. 4, online source) [ 1 , 22 , 24 , 29 , 31 , 32 , 40 , 56 , 64 , 67 ]. Our observation suggests, that the DNA methylation signature did not only result from the 1q duplication, but represented a complex pattern including the development of the structural lesion, chronic seizures, and co-morbidities [ 11 , 36 , 37 , 41 ].…”
Section: Discussionmentioning
confidence: 99%